Gender diversity among 'boys' in Papua New Guinea: Memories of sameness and difference in early childhood. (20th July 2020) - Kelly‐Hanku, Angela; Boli‐Neo, Ruthy; Aggleton, Peter; Robinson, Kerry H.; Newland, Jamee; Aeno, Herick
Abstract: Childhood is a time when children begin to constitute themselves as gendered subjects largely according to social norms that are rigidly framed within dominant discourses of heteronormative binary gender. This paper is based on the life histories of 42 sexuality and gender diverse adult men and transgender women conducted in PNG. Findings offer insight into the ways in which boys transgressed gender norms through dress, play, work within the home and in dance. We argue that gender transgression in childhood is not a contemporary phenomena and such childhood experiences of boys in PNG should be recognised as part of the country's rich cultural diversity.